(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to determine the relevancy of outdoor training in BSHM students’ development programs in terms of enhanced social communication skills, acquisition of knowledge in a particular field, development of new ideas, and network for career or job opportunities. It also highlights the advantages and disadvantages of Outdoor Training for BSHM Students. The result of this study reveals that Outdoor Training is relevant to student development. In terms of the variables mentioned above, the acquirement of knowledge in a particular field has the highest rank, followed by a network for career or job opportunities and enhanced social communication skills. Last in rank is the development of new ideas. As per the advantage of outdoor training, the result reveals that it develops personal development growth. On the other hand, the disadvantage result reveals that adopting a new environment ranked as the highest, which means that it is the biggest problem that students encounter during their training, followed by the risk of travel and prioritizing work that has the same result. The study recommended that students must participate in Outdoor Training to expand their knowledge and improve their skills. Variable Adopting New Environment (temperature/climate) is the highest rank in the disadvantage in Outdoor Training. The researchers recommend that students seek information about what place they are going. It is important to wear attire that is appropriate for the environment.